Sosialisasi Pada Guru Tentang Pemenuhan Gizi Anak Untuk Menghadapi Persiapan Pembelajaran Tatap Muka Di TK Terpadu Alif Kabupaten Jombang - Chanda Bherty; Niken Grah Prihartanti; Septi Fitrah Ningtyas; Mudhawaroh Mudhawaroh; Kolifah Kolifah (PEKAT: Jurnal Pengabdian Kepada Masyarakat, 2023)
Indonesia is a country that has been heavily affected by the Corona Virus Disease (Covid-19) outbreak. To prevent the spread of the Covid-19 virus, the government has taken various measures. The government enforces learning from home (BDR) to prevent clusters of spreading Covid-19 in schools. The many impacts caused by the government's BDR announcing the existence of a learning policy can be carried out face-to-face if the area is a green zone. The existence of this policy needs to be socialized to teachers about the fulfillment of child nutrition to face the preparation of face-to-face learning in Alif Integrated Kindergarten, Jombang Regency. This method of implementing community service, the executor gives a pre-test to all participants, after which they are given material about balanced nutrition as a preparation for face-to-face learning by the community service executors. At the end of the post-test session, it was distributed to find out whether there was an increase in participants' knowledge. Results: there was a significant increase in knowledge from the post test results, namely 78.1% of participants with good knowledge. Conclusion An increase in teacher and school knowledge is expected to be able to be passed on to parents and guardians of students as a form of face-to-face learning preparation. Keywords: Nutrition, Face-to-face Learning